IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM MENGEMBANGKAN KEMAMPUAN LITERASI SISWA KELAS V DI SD NEGERI 6 SELONG - Nadiatul Soleha, Ria; Rahman Hakim, Arif; Ulya, Manzilatul; Parsyllah Minallah, Ninda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of differentiated instruction in developing the literacy skills of fifth-grade students at SD Negeri 6 Selong. This research employed a descriptive qualitative approach. The study was conducted during the second semester of the 2025/2026 academic year, involving 20 fifth-grade students as the research participants. Data were collected through observations, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the implementation of differentiated instruction was carried out through three stages: planning, implementation, and evaluation. During the planning stage, students’ learning readiness, literacy skills, and learning interests were identified as the basis for designing learning objectives, instructional materials, learning media, and assessments. During the implementation stage, differentiation was applied to content, learning processes, and learning products according to students’ characteristics. The implementation of differentiated instruction increased students’ engagement in reading activities, group discussions, and reading comprehension according to their learning abilities. Supporting factors included the availability of instructional materials, diverse learning media, and active student participation. Meanwhile, obstacles such as differences in students’ literacy abilities, limited instructional time, and limited reading materials were addressed through individual guidance, collaborative learning, and the use of various learning media. Therefore, differentiated instruction can accommodate students’ diverse learning needs and support the development of literacy skills in elementary schools.